Cykl krakowski Maryli Szymiczkowej [właśc. Jacka Dehnela i Piotra Tarczyńskiego] jako retro krytyczne - Adam Mazurkiewicz (Literatura i Kultura Popularna, 2024)
The essay proposes treating the critical category of retro as an interpretative key for Maryla Szymiczkowa’s ‘Kraków series.’ Stories about the adventures of Zofia Szczupaczyńska make us aware of the possibility of perceiving the past not only from the perspective of nostalgia, but also allowing to maintain a reflective distance to the presented world, modeled on 19th-century realities, historically attested. The confrontation of fictional reality and its historical prototype also allows to expose the phantasmatic character of visions of the past functioning in the collective imagination. Efforts aimed at beautifying history are replaced in retro by a critical, disillusioning look at the past times by focusing the artists’ attention on what in the collective imagination has so far been replaced as casting a shadow on the idyll of the ‘good old days’ (in Szymiczkowa’s cycle it is primarily a question of the emancipation of women, objectified in patriarchal culture). By ‘disenchanting’ taboos, retro-critical issues can fulfill a culturally and socially significant function as Geertz’s ‘confused species,’ allowing for articulation and understanding of social mechanisms regulating visions of this past. What draws attention is drawn to the multi-faceted nature of the deconstruction of socially functioning visions of the past: from axiology, inscribed in the presented world, through the poetics of stories imitating the 19th-century realistic novel, to the specificity of the communicative situation.